What are the effects of changes in taxation and new types of mortgages on the real economy?: The case of Denmark during the 00's - Jesper Pedersen (Danmarks Nationalbank, 2017)
What are the effects of changes in taxation and new types of mortgages on the real economy? - The case of Denmark during the 00's What are the effects of introducing interest-only, flexible-rate mortgage contracts and a tax-freeze on housing wealth for the real- and financial economy? I study this within a medium-size DSGE model with housing, banking and financial frictions, and the coexistence of flexible-, fixed-rate and interest-only mortgage contracts. I find that the introduction and the adoption of flexible-rate and interest-only mortgage contracts together with a freeze of taxation of the housing wealth can explain around 1/3 of the real house price gap in Denmark during the period 2004-06 and 15-40 per cent of the output gap. The household debt-to-GDP would have been almost constant instead of increasing by 20 percentage points. Finally, the analysis points to a more volatile Danish economy after the implementation of the structural changes to the economy. – – Hvad er effekterne på realøkonomien af ændret boligbeskatning og introduktionen af nye låneformer? - Et case studie af dansk økonomi i 00'erne Hvad er effekterne på aktivitet og boligpriserne af introduktionen af rentetilpasningslån og afdragsfrihed og skattestoppet på boligmarkedet? Jeg analyserer spørgsmålet inden for rammerne af en DSGE-model med et boligmarked, finansielle friktioner, og banker udvidet med rentetilpasningslån og afdragsfrihed. Jeg finder, at introduktionen af de nye låntyper og ændret boligbeskatning kan forklare ca. 1/3 af boligprisens afgivelse fra en langsigtet trend i perioden 2004-06 og ca. 15-40 pct. af produktionsgabet. Husholdningernes gæld i forhold til BNP ville uden ændringer have været 20 procentpoint lavere. Endelig peger analysen på, at dansk økonomi er blevet mere volatil efter implementering af de nævnte ændringer i rammebetingelser på boligmarkedet.
Keywords: E17; E32; E62; E65; F41; 330; DSGE Models; Financial frictions; Banking; Fiscal Policy; House prices